Perbandingan Kejadian dan Faktor Risiko Hipertensi antara RW 18 Kelurahan Panembahan dan RW 1 Kelurahan Patehan - Cindy Cekti, Adiguno S.W., Sarah A.H., Khoirul A., Mohammad E.P., Datu R., Dyah A.R., Ika (Berita Kedokteran Masyarakat (BKM), 2008)
Background: The elderly makes up  10.9% and 15.5% of 720  residents  in RW  18 Kelurahan Panembahan and 645  residents  in RW  1  Kelurahan Patehan,  respectively. Most  of  the  elderly  in  both RW  districts  suffer  from hypertension and  ranks at  third place among  the 10 most prevalent diseases  in Puskesmas Kraton  in 2006. The prevalence  of  hypertension  cases always  increases year  after year  in both  kelurahan. Therefore,  hypertension gets more  concern  and  support  from  stakeholders  (the  government,  puskesmas,  LSM)  in  the  attempts  of prevention  and control,  both  in  the  form  of health  promotions and  therapy.Objective: To  determine  the  incidence  of  hypertension,  the  level  of  awareness  of  the  residents,  and  the  risk factors  that  affect  the elderly  in RW  18 Kelurahan  Panembahan and RW  1  Kelurahan Patehan, Kecamatan Kraton.Method: This  research  is a  descriptive observational  study, with  cross-sectional study  design. The  research subjects  are  the  people within  the society  of Kelurahan  Patehan  and Kelurahan panembahan  aged >60  years old. The numbers  of  samples  obtained are  110  respondents. The  instruments  of  this  research  are:  calibrated aneroid sphygnomanometer, weighing  scale, measuring  tape,  and  questionnaires. Data analysis  is  done with the Chi-square  test method and Fisher Exact  test by  using  crosstabs,  in addition  to  using  the  compare mean independent T-test.Results: Hypertension  is  found  to  affect  59.3%  of  the  elderly  population  in RW  1 Patehan and  55.36% of  thepopulation  in RW  18 Panembahan.  Interestingly,  this  corresponds  to  the prevalence  data collected  by JNC  VII which states  that half  of  the  population  aged  60-69  years  old suffers  from hypertension. Further analysis  done within  this  research  shows  that  there  is  no  significant  correlation between  the  incidence  of  hypertension  and the  risk  factors  of BMI,  smoking,  exercise,  diets with  high  salt  content,  and  coffee.  In RW  18  Kelurahan Panembahan,  the  p  values  for  the  risk  factors mentioned  above  are  0.159;  1.000;  1.000;  0.367;  and  0.446 respectively. In RW 1 Kelurahan Patehan,  the p values are 0.181; 1.000; 0.901; 1.000; and not analyzable. Based on  interview,  the  amount of  salt consumption  in both RW  is  somewhat difficult  to determine  in  the  field, as  the food is cooked and prepared in each household for several family members at a time. It is difficult for the subjects to  estimate how many  tablespoonfuls  of salt  is  used  in  the  dishes  because  subjects  are   accustomed  to  use rough hand measurements  in  taking salt.  In addition  to  that, parts of  the society  in  the  target environment prefer to  buy  instant  foods. The  same applies  to  coffee  consumption;  it  is hard  to estimate  the amount  consumed because  it  is not  a  routine  activity, and  each  individual  differs  in  the sense  of how much coffee  taken each  day and which  type  of  coffee  is  used. The  consumption of  cigarettes everyday  also  differs  between  one  individual and  the  other and  the average  amount  is  below  that which  can  cause  increase  in blood  pressure.Conclusion: The quantitative  study  in  this  research,   supported with  a  qualitative  study,  shows  that aspects  of behavior  are not  risk  factors  that can  cause hypertension.  The  incidence  of hypertension  in Kelurahan Patehan and Panemahan  is  related  to age. Therefore,  research  is  done  regarding age  distribution and  hypertension incidence  in  the  region, preceded  by  improvements  in  the  instruments used  to determine  the  levels  of salt  and caffein consumption  and  levels  of  stress. The  residents  of RW  1, Kelurahan Patehan  and RW  18,  Kelurahan Panembahan,  Kecamatan Kraton may  serve  as models  to  illustrate  that  there  is  no  correlation  between  risk factors  and  incidence of  hypertension  in  an urban  area with  high  levels  of stress. Therefore,  there  is  the  need to do  further  research  regarding cultural  (Kraton)  influences  city  toward  another city  center  settlements  stress factors  that are  related  to  hypertension.Keywords: elderly,  hypertension,  risk  factors, Kelurahan Patehan and Panembahan, Kecamatan Kraton